Carbon Stock Analysis in Mangrove Vegetation in Selat Baru Village, Bengkalis Regency, Riau Province - Siagian, Aron Girgir Parade; Siregar, Sofyan Husein; Yoswaty, Dessy (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2026)
Mangrove forests play a crucial ecological role in coastal ecosystems. One of its ecological functions is that mangroves absorb and store carbon, thereby reducing carbon emissions. The increase in atmospheric CO2 levels is a result of human activities, both directly and indirectly. This study aims to assess mangrove stand density, determine differences in mangrove stand density and carbon stocks between stations, and examine the relationships between mangrove stand density and biomass, carbon stocks, and CO2 absorption in the mangrove area of ​​Selat Baru Village, Bengkalis Regency, Riau Province. This research was conducted in November 2024 in Selat Baru Village, Bengkalis Regency, Riau Province. The method used in this study was a survey. To determine the relationship between mangrove tree density and carbon stock, a regression test was performed. Mangrove Stand Density ranged from 877.78 - 1,211.11 ind/ha. Mangrove biomass ranged from 22.62 to 30.16 tons/ha. Carbon Stock ranges from 10.63-14.19 tons/ha. CO2 absorption ranges from 38.98-51.98 tons/ha. The density of mangrove stands and carbon stocks show a moderate relationship, as indicated by the correlation coefficient (r) of 0.736.